2020
DOI: 10.15195/v7.a8
|View full text |Cite
|
Sign up to set email alerts
|

The U.S. Occupational Structure: A Social Network Approach

Abstract: We propose a new approach to study the structure of occupational labor markets that relies on social network analysis techniques. Highly detailed transition matrices are constructed based on changes in individual workers' occupations over successive months of the Current Population Survey rotating panels. The resulting short-term transition matrices provide snapshots of all occupational movements in the U.S. labor market at different points in time and for different sociodemographic groups. We find a significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Occupation is associated with depression through job-related psychosocial stressors and socioeconomic status [33][34][35], and occupation-related travel expands the geographic reach of occupational and social networks [36][37][38]. Therefore, we incorporated information from the American Community Survey occupation by industry tables into our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Occupation is associated with depression through job-related psychosocial stressors and socioeconomic status [33][34][35], and occupation-related travel expands the geographic reach of occupational and social networks [36][37][38]. Therefore, we incorporated information from the American Community Survey occupation by industry tables into our analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, the transfer of human capital is not the same among all occupations, which explains the significant heterogeneity in worker flows from one occupation to another (Harper, 1995; Poletaev & Robinson, 2008; Villarreal, 2020). In this sense, it has been shown that people tend to migrate between occupations requiring similar skills and performing similar tasks (Cortes & Gallipoli, 2018; Fedorets, 2019; Parrado et al.…”
Section: Discussion Of Main Arguments and Findingsmentioning
confidence: 99%
“…The possible loss of human capital makes on-the-job seekers (Deng, Li, & Shi, 2022) and workers with solid occupational commitment (Otto, Dette-Hagenmeyer, & Dalbert, 2010) less willing to change occupations. However, the transfer of human capital is not the same among all occupations, which explains the significant heterogeneity in worker flows from one occupation to another (Harper, 1995;Poletaev & Robinson, 2008;Villarreal, 2020). In this sense, it has been shown that people tend to migrate between occupations requiring similar skills and performing similar tasks (Cortes & Gallipoli, 2018;Fedorets, 2019;Parrado et al, 2007;Poletaev & Robinson, 2008;Robinson, 2017), mitigating the possible loss of specific human capital and, therefore, wage loss (Bachmann et al, 2020;Gathmann & Sch€ onberg, 2010;Poletaev & Robinson, 2008;Robinson, 2017).…”
Section: Human Capitalmentioning
confidence: 99%
“…Having similar cultural resources, such as tastes, knowledge bases, political attitudes, and worldviews, makes it easier for spouses to have conversations, offer each other social confirmation, partake in joint activities, and reduce potential conflict in family decision-making (Kalmijn 1994(Kalmijn , 1998Schwartz 2013;Streib 2015). Due to increasing occupational segregation by socioeconomic status and growing wage inequalities across occupations, occupations are increasingly linked to attitudes, tastes, lifestyles, and life trajectories (Cambois et al 2011;Rivera 2012;Villarreal 2020;Weeden and Grusky 2005).…”
Section: Occupation As a Key Correlate Determining Partner Selectionmentioning
confidence: 99%